Telehealth Use and Hospital Readmission Rates in Long-term Care Facilities in Southeastern Minnesota During the COVID-19 Pandemic - Melissa H. Bogin, MD; Anupam Chandra, MD; Jennifer Manggaard, CCRP; Bjoerg Thorsteinsdottir, MD; Gregory J. Hanson, MD; Paul Y. Takahashi, MD, MPH (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2022)
Objective: To determine whether the length of a telehealth visit predicted the risk of hospital readmission at 30 days in skilled nursing facilities (SNFs) in southeastern Minnesota during the coronavirus disease 2019 pandemic. Patients and Methods: This was a retrospective cohort study conducted in SNFs located in southeastern Minnesota from March 1, 2020 through July 15, 2020. The primary outcomes included hospitalization within 30 days of a video visit, and the secondary outcome was the number of provider video visits during the stay at an SNF. The primary predictor was the duration of video visits, and we collected the data regarding other known predictors of hospitalization. We used the χ2 test for categorical variables and multivariate conditional logistic regression. Results: We included 722 patients (mean age, 82.8 years [SD, 10.8 years]). Of those, 76 SNF residents (10.5%) were rehospitalized within 30 days. The average length of a video visit was 34.0 minutes (SD, 22.7 minutes) in admitted residents compared with 30.0 minutes (SD, 15.9 minutes) in nonadmitted residents. After full adjustment, there was no difference in the video visit duration between admitted and nonadmitted residents (odds ratio, 1.01; 95% CI, 0.99-1.03). The number of subsequent provider video visits was 2.26 (SD, 1.9) in admitted residents vs 1.58 (SD, 1.6), which was significant after adjustment (odds ratio, 1.17; 95% CI, 1.02-1.34). Conclusion: There was no difference in the length of video visits for hospitalized SNF residents vs those who were not hospitalized within 30 days of a video visit. There were more visits in residents with hospital readmission. This may reflect the acuity of care for patients requiring a hospital stay. More research is needed to determine the ideal use of telehealth during the coronavirus disease 2019 pandemic in the postacute and long-term care environment.